W.B. Hvland, Wilmington City Code: The Ordinances of the City of Wilmington, Delaware 689 (1885) - (:unkn) unknown (My University, 1885)
Required supplying retailers to be in kegs, not more than twenty-five pounds, carefully enclosed in good bags, or by putting a sheet of canvas under and around the kegs. When transporting gunpowder the carriage shall contain no more than ten kegs as described above.
Keywords: GUNPOWDER - STORAGE; GUNPOWDER - TRANSPORTATION